Nutritional and metabolic parameters of sheep fed extruded roughage - Oliveira, Karla Alves; Siqueira, Marco Túlio Santos; Oliveira, Marcela Rodrigues de; Dutra, Thamiris Oliveira; Sousa, Luciano Fernandes; Macedo Júnior, Gilberto de Lima (Scientia Agraria Paranaensis, 2022)
The search for technologies to increase productivity of the herds, without increasing production costs, brings a positive highlight to extruded feeds, since these products act to maximize digestive efficiency. The objective was to evaluate the effect of using different levels of inclusion of extruded roughage to replace corn silage on nutritional and metabolic parameters in sheep. For this, 20 ewes aged over three years were used, housed in metabolic cages, distributed in a completely randomized design in four treatments, which consisted of different levels of inclusion of extruded roughage to replace corn silage (20%, 40%, 60% and 80%). Dry matter intake (DMI) and water intake were calculated by the difference between what was offered and what was left over. Blood glucose and energy and protein metabolites were obtained through blood collection by jugular venipuncture and subsequent laboratory analyses, and feeding behavior by observation every 5 min. for 24 h. DMI and water intake increased linearly with the inclusion of extruded roughage in the diet. The greater inclusion of extruded roughage reduced the total chewing time, consequently increasing the efficiency of ingestion, rumination and total chewing. The inclusion of extruded roughage in the diet of sheep increases the dry matter intake, without reducing the digestibility of nutrients, reducing the time spent on chewing.